Odisha’s agricultural export footprint - Kamar, Abdul; Kumar Padhee, Arabinda; Pradhan, Mamata; Roy, Devesh (International Food Policy Research Institute, 2025)
Odisha’s agricultural exports are rising steadily, yet they remain highly concentrated in a few products and districts. Shrimp continues to dominate, while cotton and rice are gradually emerging as important contributors. Notably, the share of agriculture in Odisha’s total merchandise exports has nearly doubled from 4% in 2021–22 to 7% in 2024–25,.